Research, Development and Innovation for European Urban Challenges – Role, aims and output for RD&I EU programme. - Clerici, Paola; Annunziato, Mauro (ObIES, 2017)
Paper will present the most significative European RD&I programme for urban areas. Europe is one of the most urbanized continents in the world; more than two thirds of Europeans live in urban areas and this percentage continues to grow. European cities play a crucial role as engines of the economy, as places of connectivity, creativity and innovation, and as centres of services for their surrounding areas. Due to their density, cities offer a huge potential for energy savings and a move towards a carbon-neutral economy. Cities are, however, also places where problems such as unemployment, segregation and poverty are concentrated. Then, administrative boundaries of European cities no longer reflect the physical, social, economic, cultural or environmental reality of urban development and new forms of flexible governance are needed. However we could say that there is a common idea in Europe on the role which cities can play for the territorial development to be based on a balanced economic growth and territorial organisation of activities, with a polycentric urban structure; on build strong metropolitan regions and other urban areas that can provide good accessibility to services of general economic interest; on characterisation of compact settlement structure with limited urban sprawl; on provide a high level of environmental protection and quality in and around cities. To turn the threats into positive challenges European cities follow different development trajectories and their diversity has to be exploited. The European Union does not have a direct policy competence in urban and territorial development, but the last two decades have witnessed an increasing importance of the European level in both urban and territorial development. RD&I programmes have been developped to support and promote urban and territorial development. The article will investigate which contributes have been given by main RD&I programmes and will consider their replicabilty and/or transferability out of Europe.